1977
DOI: 10.1172/jci108899
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Plasma Transport, and Cellular Retention of Cobalamin Analogues in the Rabbit

Abstract: A B S T R A C T Analogues of cobalamin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
69
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Our studies have demonstrated that most B12-compound found in spir ulina tablets is pseudo-B12 inactive for humans (19). IF involved in the intestinal absorption of B12 strictly rec ognizes the structure of the B12 molecule (30). Pseudo B12 has been reported to show moderate affinity to IF among various B12-compounds (28).…”
Section: Purification and Characterization Of B12 Compounds From Edibmentioning
confidence: 63%
“…Our studies have demonstrated that most B12-compound found in spir ulina tablets is pseudo-B12 inactive for humans (19). IF involved in the intestinal absorption of B12 strictly rec ognizes the structure of the B12 molecule (30). Pseudo B12 has been reported to show moderate affinity to IF among various B12-compounds (28).…”
Section: Purification and Characterization Of B12 Compounds From Edibmentioning
confidence: 63%
“…Radioassays using intrinsic factor from pig stomach are available commercially and allow for rapid determination of 'true vitamin B 12 ' in a large number of samples. Both intrinsic factor and haptocorrin have a high affinity for CBL but haptocorrin has a greater affinity for analogs than intrinsic factor (Kolhouse and Allen, 1977;Adjalla et al, 1993). Measurements of CBL in feed and omasal digesta by LC-MS or by a radioassay using intrinsic factor as binding protein were highly correlated.…”
mentioning
confidence: 98%
“…Approximately one-quarter of Cbl in plasma is bound to TC, whereas the rest circulates bound to plasmatic HC that can enter only hepatocytes. All three proteins carry a single Cbl molecule and show high affinity to the ligand (6) but differ in specificity for Cbl and its analogues produced by microorganisms (7).…”
mentioning
confidence: 99%